Impact of creativity to organizational competitiveness - Sulaiman, Ibrahim Fahad; Hashim, Che Noraini; Ibrahim, Mohd Burhan; Syed Hassan, Sharifah Sariah; Oluwatosin, Owolabi Sunday (Centre for Promoting Ideas, USA, 2015)
Organizations increasingly seek to improve creative capability to enhance their performance. Therefore the impact towards competitiveness becomes increasing important as most learning and training has focused on accumulation of knowledge rather than ensuring practicable skill and knowledge transfer that is central to creativity. This study reported the impact of creativity to organizational competitiveness. The review confined to performance enhancement of creativity leading to organizational competitiveness which is a necessity to match with the transitional changes from knowledge based to creativity. This review unveils organizational performance for stronger and more inclusive growth based on key priorities that complementarily provide the basis for a comprehensive and action-oriented approach to innovation from knowledge creation to problem solving. Creativity leading to innovation was found to be an integral part of organizational process. However, this findings strengthens knowledge creation and innovation diffusion to enhance organizational competitiveness using a modified version of Kianto Model.